Modulação PWM vetorial multidimensional para conversores de dois níveis com número ímpar de fases - Freitas, Sabrina Alves de (2021)
In this paper is proposed a space vector pulse width modulation (SVPWM) algorithm for multiphase drive with any odd number of phases and symmetrical phase distribution. The SVPWM consists of choosing the appropriate active and null spatial voltage vectors and determining the time intervals of application for each of these vectors, so that a given reference voltage vector is synthesized by the inverter as the mean value in a switching period. In a three-phase drive system, the most appropriate active voltage vectors for synthesizing a given reference vector are easily observed graphically, since the vectors are of dimension two, and, consequently, visual ized in a plane. However, for machines with more than three phases, the space vector in which the vectors are located is of larger dimensions, which makes a graphic visualization of the vec tors difficult. As an example, in a five-phase drive, the dimension of the space vector is four and, although the projection of these vectors in two planes still allows some degree of graphical visualization, the identification of the most suitable active vectors is not so obvious, specially if the reference voltage vector has projection in both planes (that means a control system with harmonic injection). In this work, an algorithm based on the reference phase voltages for fast identification of the most suitable active vectors to be applied to synthesize a given reference voltage vector is proposed. Such an approach allows a quick identification of the active voltage vectors that define a certain sector. This method, in addition to simplicity, requires low storage space and processing power, which makes it suitable for real-time operation. Furthermore, a SVPWM requires the inversion of matrices of order equal to the dimension of the space vector in order to calculate the time application of the vectors. Although in the three-phase case this calculation is simple, as it is the inversion of an order two matrix, in machines with a larger number of phases the order of the matrix increases and this inversion requires large processing time, which can become unfeasible in real-time operations. Beside, there is numerical problems in calculating the inverse matrix for large order matrices. In this work, it is shown that due to the existing symmetry in all sectors of the SVPWM, it is possible to avoid matrix inversion. Hence, the main contributions in this paper is a SVPWM modulator for a multiphase two level inverter drive system with any odd number of phases.